A randomized comparative trial of first-dose response to Angiotensin- Converting Enzyme Perindopril and Captopril in Indonesian heart failure patients (Medical Journal of Indonesia, 2002)
Several large placebo-controlled trials have confirmed that angiotensin converting enzyme (ACE) inhibitors significantly reduce mortality aid morbidity in all functional grades of congestive heart failure (CHF), nevertheless only a proportion of patients who may benefit from treatment are priscribed an ACE inhibitor. One of the perceived difficulties is the occurrence of first-dose hypotension in susceptible patients. A double-blind, randomised, single-dose therapy, parallel-group study was conducted with the aim to compare the first-dose responses to low dose ACE inhibitors captopril and perindopril in patients with stable chronic heart failure. Seventy patients (New York Heart Association class I-IV) were included. Blood pressure was recorded every 15 minutes 2 hours before starting treatment. The mean of these readings was taken as the baseline blood pressure. Patients were randomised to receive a single-dose of captopril 6.25 mg or perindopril 2 mg. After taking the drug, blood pressure was monitored every 15 minutes for 2 hours, every 30 minutes during 5 hours then hourly after 2 hours. The maximum mean arterial pressure fall from baseline of perindopril was 0.85 mmHg compared to captopril 4.60 mmHg. The maximum mean systolic fall from baseline of perindopril was 3 '31 'mmHg compared to captopril 6.76 mmHg while the maximum mean diastolic fall from baseline of perindopril was 1.08 mmHg compared to captopril 2.63 mmHg. The hypotensive effect of the captopril group started soon after dosing and reached its maximum after 1 to 2 hours while perindopril showed slight reduction of systolic after 1 hour and slight reduction of diastolic after 4 hours. Compared to captopril, perindopril seemed to be less likely to cause first-dose hypotension in patients with heart failure. (Med J Indones 2002; 11: 19-23)Keywords: first dose hypotension, perindopril, captopril, chronic heart failure